Improved Mycology Media Formula of Corn and Cow’s Hair For Accelerate Superficial Mycosis Growth - Ratih Dewi Dwiyanti; Leka Lutpiatina (Medical Laboratory Technology Journal, 2021)
Potato Dextrose Agar is growth and identification media of fungi that cause superficial mycoses, including Trichophyton rubrum and Trichophyton mentagrophytes with 10–14 days growth period. Modification media is needed to accelerate the growth of the fungus. Zea mays saccharata has a high carbohydrate, and cow’s hair contains high keratin, which can be used as a nutrient to replace fungal growth media. The study aimed to obtain a modified media formula containing Zea mays saccharata as a substitute for dextrose and cow's hair as a source of keratin to accelerate the growth of Trichophyton rubrum and Trichophyton mentagrophytes fungi. The modified media formula is mixing of Zea mays saccharata 15% to 25%, and cow's hair 20mg to 35mg. Acceleration of growth time based of when found microconidia and macroconidia, diameter measurements, and observations of texture and colonies color of Trichophyton rubrum and Trichophyton mentagrophytes. The study results are Zea mays saccharata media with the addition of cow hair for Trichophyton rubrum grew 11 days with 10%+20mg formula and grew only seven days with 25%+35mg formula. Modified media for Trichophyton mentagrophytes grew seven days for 10%+20mg formula, while it was only three days with 25%+35mg formula. The media formula with the fastest growth rate for Trichophyton rubrum and Trichophyton mentagrophytes was at a concentration of 25%+35mg. The Advanced Modified Media can become a patent medium for faster growth of superficial fungi at a lower cost. Further research needs to be done on how long this media can be stored for long-term use.